INHERITANCE CONFLICT IN ISLAMIC LAW - Doris Rahmat; Santoso Budi NU (Universitas Slamet Riyadi, 2021)
Conflicts between heirs also often occur because of the natural attitude of humans who do not want to give in and want to win themselves, in order to get the largest share of the inheritance among other families. Problem Formulation How is inheritance conflict in Islamic law The purpose of this research is to find out inheritance conflict in Islamic law.The method used in this study is a sociological juridical approach, namely an approach to the problem through legal research by looking at the legal reality in practice, then connecting it with the facts that exist from the problem to be examined.The problem of the distribution of inheritance has become a phenomenon that often occurs in society from the past until now. Because the distribution of inheritance is very sensitive. Often a conflict in the midst of the family. However, people who are Muslim apply to the Islamic Inheritance Law, the point is that inheritance issues can trigger the rift in family relationships. This happens if the distribution of the inheritance is not in accordance with the rules and signs that have been set by Allah in the Qur'an